2003
DOI: 10.1207/s1532690xci2104_4
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Path Length: Fourth-Grade Children's Developing Abstractions for Linear Measurement

Abstract: This article describes how children build increasingly abstract knowledge of linear measurement, emphasizing ways they relate space and number. Assessments indicate children struggle to understand measurement, especially concepts related to complex paths as in perimeter tasks. This article draws on developmental accounts of children's knowledge of measurement to describe the coordination of cognitive processes as a progression through increasingly abstract layers of strategy (Clements, 2003;Lehrer, 2003) withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 28 publications
2
27
0
2
Order By: Relevance
“…According to Barrett and Clements (2003), mathematical tasks involving the following components are important to support children's strategies for abstracting length measurement: recognition of integral relationships among unit of length, sides of polygons, and perimeter measurement; and stimulation of the use of partitive, iterative, and counting strategies. Moyer (2001) proposed that conceptual understanding of the relationship between the perimeter and area of a rectangle depended on the ability to distinguish the attributes and explain the processes of the two measurements.…”
Section: Reasoning With Regard To the Perimeter And Area Of A Rectanglementioning
confidence: 99%
See 1 more Smart Citation
“…According to Barrett and Clements (2003), mathematical tasks involving the following components are important to support children's strategies for abstracting length measurement: recognition of integral relationships among unit of length, sides of polygons, and perimeter measurement; and stimulation of the use of partitive, iterative, and counting strategies. Moyer (2001) proposed that conceptual understanding of the relationship between the perimeter and area of a rectangle depended on the ability to distinguish the attributes and explain the processes of the two measurements.…”
Section: Reasoning With Regard To the Perimeter And Area Of A Rectanglementioning
confidence: 99%
“…Moyer (2001) proposed that conceptual understanding of the relationship between the perimeter and area of a rectangle depended on the ability to distinguish the attributes and explain the processes of the two measurements. Barrett and Clements (2003) suggested that knowledge of 2-D geometry improves children's conceptualization of perimeter. We thus hypothesized that an instructional intervention integrating spatial geometry with area measurement in which children are guided to pay attention to the relationship between number and space (e.g.…”
Section: Reasoning With Regard To the Perimeter And Area Of A Rectanglementioning
confidence: 99%
“…Furthermore, Barrett and Clements (2003) and Malloy (1999) argued that a better concept of area and perimeter grounded on acquisition of geometric concepts. Thus, it is argued that children's application of area formulas and their performance in identifying geometric shapes and in modifying their erroneous solutions of area measurement are related to the quality of understanding of area measurement.…”
Section: Children's Strategy Used For Solving Area Measurement Problemsmentioning
confidence: 99%
“…We describe this as Consistent Length Measurer (CLM) in Table 1. As children reflect on their own operations with collections of units to measure using ever-smaller units they make goal-directed decisions about ways to curtail their motion along objects (Barrett & Clements, 2003). Children gradually expect a collection of units to be conserved as they develop what Steffe (1991) called a conceptual ruler-the ability to mentally iterate units that are not perceptually available along the object-as early as grade 3.…”
Section: Empirical Basis For the Hypothetical Learning Trajectorymentioning
confidence: 99%
“…Children gradually expect a collection of units to be conserved as they develop what Steffe (1991) called a conceptual ruler-the ability to mentally iterate units that are not perceptually available along the object-as early as grade 3. As children in grades 4 and 5 reflect on their activities with path length problems, they integrate motions, drawings, and verbal narratives to act on an internal image of a nested sequence of units (Barrett & Clements, 2003;Bragg & Outhred, 2004;Chiu, 1996;Fischbein, 1993;Outhred & Mitchelmore, 2004). Thus, more sophisticated levels may exist beyond Conceptual Ruler measurer (CR).…”
Section: Empirical Basis For the Hypothetical Learning Trajectorymentioning
confidence: 99%